\(4\left(x^2-15x+50\right)\left(x^2-18+72\right)-3x^2\)
\(=4\left(x+5\right)\left(x+10\right)\left(x+6\right)\left(x+12\right)-3x^2\)
\(=4\left[\left(x+5\right)\left(x+12\right)\right]\left[\left(x+10\right)\left(x+6\right)\right]-3x^2\)
\(=4\left(x^2+17x+60\right)\left(x^2+16x+60\right)-3x^2\)
Đặt \(x^2+16x+60=a\), ta có:
\(4\left(a+x\right)\left(a\right)-3x^2\)
\(=4a^2+4ax-3x^2\)
\(=4a^2-2ax+6ax-3x^2=2a\left(2a-x\right)+3x\left(2a-x\right)\)
\(=\left(2a-x\right)\left(2a+3x\right)\)
Thay a vào ta có: \(\left[2\left(x^2+16x+60\right)-x\right]\left[2\left(x^2+16x+60\right)+3x\right]\)
\(=\left(2x^2+31x+120\right)\left(2x^2+35x+120\right)\)
S_1=1/1.2+1/3.4+1/5.6+...+1/99.100
=1‐1/2+1/3‐1/4+1/5‐1/6+...+1/99‐1/100
=﴾1+1/3+1/5+...+1/99﴿‐﴾1/2+1/4+1/6+...+1/100﴿
=﴾1+1/2+1/3+1/4+1/5+1/6+...+1/99+1/100﴿‐2﴾1/2+1/4+1/6+...+1/100﴿
=﴾1+1/2+1/3+1/4+...+1/100﴿‐﴾1+1/2+1/3+..+1/50﴿
=1/51+1/52+1/53+..+1/100 ﴾1﴿
S_2=1/51+1/52+1/53+..+1/100 ﴾2﴿
Từ ﴾1﴿,﴾2﴿=> S_1/S_2=1
Vậy S > 1/2